RELIABILITY ANALYSIS OF HELICOPTER BLADE ROTOR PLAY BELL 412 USING NORMAL DISTRIBUTION METHOD - Rastra Arif Pradana; Kris Hariyanto; Fajar Khanif Rahmawati (Vortex, 2020)
At the beginning of operation, a main rotor blade on helicopter is certainly in the best condition. When it gets older, the main rotor blade condition will decrease because of the presence of bent, material fatigue and human error during operation. Based on the background, it is necessary to identify the level of reliability of main rotor blade on the Bell 412 helicopter using the normal distribution method. The research data were the age of components of main rotor blade on Bell 412 helicopter during 27 years.Based on the analysis of calculation of the reliability level, employing the normal distribution method and using Microsoft Excel, the reliability value (R) of all serial numbers of Bell 412 helicopter main rotor blade was 99%, which indicates the reliability of the Bell 412 helicopter main rotor blade is very good.